Implementasi Prinsip Green Hospital pada Desain Lanskap Gerbang Masuk RSD DR A Dadi Tjokrodipo Bandar Lampung - Hutriani, Ina Winiastuti; Ali, Muhammad Saddam; Amanda, Zulvita (http://arl-faperta.ipb.ac.id/, 2024)
dr A Dadi Tjokrodipo Regional Hospital Bandar Lampung is one of the hospitals whose mission to create a clean, green and pollution-free hospital environment. This mission is in line with the Program of the Ministry of Health Republic of Indonesia, namely The green hospital Program, a hospital which has designed, built/renovated, operated and maintained by considering the principles of health and a sustainable environment. The implementation of the green hospital principles at dr A Dadi Tjokrodipo Regional Hospital has not been optimal, one area which is the landscape of the hospital gate. This study aims to provide recommendations in the landscape design of hospital gate by implementing the principles of green hospital to support dr A Dadi Tjokrodipo Regional Hospital towards green hospital in Bandar Lampung. This study used design method modified from LaGro (2013) which consisted of a site survey stage; literature study; analysis-synthesis stage and conceptual design stage. Based on the results of this research, the implementation of green hospital principles in the landscape design of the dr A Dadi Tjokrodipo Regional Hospital applied to two major criteria, namely design and construction criteria and operational criteria. Design and construction criteria implemented include land development criteria and healing garden criteria. The operational criteria applied include transportation criteria and green material procurement criteria. Design recommendations based on the principle of green hospital can be followed up in the form of detailed engineering design (DED) documents and proposed budget plans so that the design can be implemented in the field.